A case report of troubleshooting against bleeding from inferior vena cava injury - Tadamasa Shibuya; Toru Inoue; Tadasuke Ando; Toshitaka Shin (IJU Case Reports)
Introduction We report a case of troubleshooting against bleeding from an inferior vena cava injury using a gelatin–thrombin matrix. Case presentation A 58‐year‐old man underwent robot‐assisted partial adrenalectomy for a right adrenal adenoma causing subclinical Cushing's syndrome. During the surgery, while dissecting between the adrenal gland and the inferior vena cava, bleeding occurred secondary to an inferior vena cava injury. Despite attempts at hemostasis, applying a human fibrinogen–thrombin patch and suturing were both difficult because of poor vision secondary to the bleeding. Hemostasis was ultimately achieved using a gelatin–thrombin matrix, which was accurately placed on the bleeding point using gauze. Open conversion was hence avoided, allowing the completion of the surgery as planned. Conclusion Gelatin–thrombin matrix may be effective for managing relatively small inferior vena cava injuries.